2014
DOI: 10.5901/mjss.2014.v5n16p567
|View full text |Cite
|
Sign up to set email alerts
|

The Perpetrators of Workplace Bullying in Schools: A South African Study

Abstract: This study investigates workplace bullying (WPB)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
(94 reference statements)
0
2
0
Order By: Relevance
“…ther than employees [10]. Previous research showed that targets tended to be high in n roticism [11], and perpetrators tended to be aggressive [9], disagreeable [12] and less scientious [13]. Cross-sectional research on the work environment found that WB pe tration is higher when organizational trust and justice are low [10]; when there is w spread inappropriate social conduct [14] and team fit is low [15]; when leaders are ab [16], or passive avoidant [17] and when employees are being bullied [18,19].…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 98%
See 1 more Smart Citation
“…ther than employees [10]. Previous research showed that targets tended to be high in n roticism [11], and perpetrators tended to be aggressive [9], disagreeable [12] and less scientious [13]. Cross-sectional research on the work environment found that WB pe tration is higher when organizational trust and justice are low [10]; when there is w spread inappropriate social conduct [14] and team fit is low [15]; when leaders are ab [16], or passive avoidant [17] and when employees are being bullied [18,19].…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 98%
“…Previous studies showed that the prevalence rates of WB perpetration vary between 2.8% [2], 4% [3], and 5% [4]. The impact of WB on targets stretches from sleep problems [5,6], and mental health issues [7] to extreme suicidal thoughts [8]; perpetrators are psychologically distressed [9] and suffer mental illnesses [10]. While we do not know much about perpetrators' physical activities, a previous study showed that they had elevated adverse physical symptoms, including trouble sleeping, and tended to be supervisors rather than employees [10].…”
Section: Introductionmentioning
confidence: 99%